2022
DOI: 10.3389/fmolb.2022.858316
|View full text |Cite
|
Sign up to set email alerts
|

Local Ion Densities can Influence Transition Paths of Molecular Binding

Abstract: Improper reaction coordinates can pose significant problems for path-based binding free energy calculations. Particularly, omission of long timescale motions can lead to over-estimation of the energetic barriers between the bound and unbound states. Many methods exist to construct the optimal reaction coordinate using a pre-defined basis set of features. Although simulations are typically conducted in explicit solvent, the solvent atoms are often excluded by these feature sets—resulting in little being known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Following ref. 54 , we also investigated the role of the ionic density and found that it does not play a relevant role in this system (see Supplementary Information ( SI )).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Following ref. 54 , we also investigated the role of the ionic density and found that it does not play a relevant role in this system (see Supplementary Information ( SI )).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…While it appears that the cutoff COM distance chosen could have been reduced for the OA‐G6 and OA‐G3 systems, it was found in previous work (Ref. 39) that for these systems, rebinding can often occur below a 0.7 nm d COM distance. The tutorial repository associated with this article 40 contains everything needed to reproduce the results here, including: code for the custom distance metric and boundary condition, scripts to run the binding and unbinding simulations, scripts to plot the d COM for reactive trajectories, and scripts to extract the rebinding simulation starting poses.…”
Section: Methodsmentioning
confidence: 91%
“…This is caused by the rare occurance of high probability walkers crossing into the unbound state in unbinding simulations, which introduces large jumps in transition fluxes and unbinding rates. Interestingly, our previous work sought to identify microscopic determinants of these differences in probability and found that there was a correlation between guest‐ion interactions and the unbinding weight of a given trajectory for several SAMPL systems 39 . Specifically, rare high‐probability trajectories that contributed most significantly to the unbinding rate had a lower amount of guest‐ion interaction than the far more numerous low‐probability trajectories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation